EFFECTIVENESS OF DISCOVERY LEARNING MODEL TOWARD MATHEMATICS LEARNING OUTCOMES IN STUDENTS CLASS VII - Irma Puji Lestari; Uus Kusdinar (Universitas Ahmad Dahlan, 2018)
The teacher-centered learning process of mathematics will cause students not to be actively involved in the learning process. Discovery Learning model is expected to change the learning activities of teacher-oriented into student oriented so that the effect on student learning outcomes. This study aims to determine the Discovery Learning model of mathematics learning outcomes of students of class VII SMP Muhammadiyah 2 Yogyakarta, even semester of the academic year 2016/2017. This type of research is experimental research using Posttest-Only Control Design. The research sample is class VII E as an experimental class, and class VII B as a control class was taken by cluster random sampling technique. The experimental class is the class that is treated using the Discovery Learning model, while the control class is a class that uses the direct learning model. In this study, data collection using written tests and instruments of data collection using test questions. The data obtained were analyzed using a t-test. The study results at a significant level of 5%, and degrees of freedom = 51 indicate (1) there are differences in learning outcomes between students using the Discovery Learning model, and students using direct learning models. This is shown by ttable = 2,00758, and tcount = 4,24125, so tcount > ttable, and (2) Discovery Learning model is more effective than learning using direct learning model. This is indicated by the value ttable = 1.67528, and tcount = 4.24125 so that tcount > ttable.